Integrated discovery of FOXO1–DNA stabilizers from marine natural products to restore chemosensitivity to anti-EGFR-based therapy for metastatic lung cancer. Issue 2 (14th December 2016) - Sun, Yingjia; Ai, Xinghao; Hou, Jingwen; Ye, Xiangyun; Liu, Ruijun; Shen, Shengping; Li, Ziming; Lu, Shun
Abstract : Small-molecule marine natural products are identified to selectively recognize and stabilize the DNA-binding conformation of FOXO1, an oncogenic transcription factor. Abstract : The transcription factor forkhead box O1 (FOXO1) negatively regulates activated EGFR signaling by turning on the gene expression of tumor suppressor Kruppel-like factor 6. Here, we propose that the chemosensitivity to anti-EGFR-based lung cancer therapy can be restored by stabilization of the FOXO1–DNA complex architecture using small-molecule marine natural medicines. A synthetic protocol that integrates computational ligand–protein–DNA binding analysis and an experimental fluorescence binding assay was applied against a large library of structurally diverse, drug-like marine natural products to discover novel stabilizers of DNA-bound FOXO1 conformation. The screening utilized chemical similarity analysis to exclude structurally redundant compounds, and then carried out high-throughput molecular docking and computational binding analysis to identify potential marine natural product candidates. Consequently, eight commercially available hits were selected and tested in vitro, from which four marine natural product compounds (tanzawaic acid D, hymenidin, cribrostatin 6 and barbamide) were found to have high or moderate potency to selectively bind to the FOXO1 DNA-binding domain (DBD) in the presence of its cognate DNA partner. Atomistic molecular dynamics (MD) simulations revealed that the identified stabilizers do not directly interact with DNA; instead, they can effectively stabilize the free FOXO1 DBD domain in the DNA-bound conformation and thus promote the binding of FOXO1 to DNA.